Penerapan Arsitektur Islam pada Desain Pusat Thibbun Nabawi di Kota Makassar - Ovy Uniarti Ananda; Alfiah, Alfiah; Sam, Mukhlishah (TIMPALAJA : Architecture Student Journals, 2024)
Abstract_non-medical diseases have become a common problem among people from various walks of life. From an Islamic perspective, Thibbun Nabawi therapy can treat this disease. The increasing number of visitors and the growth of Islamic alternative health facilities in Makassar City present an opportunity to enhance health facilities, specifically the Thibbun Nabawi medical center. The research method employs data collection methods such as journals, books, and information related to Thibbun Nabawi treatment. Additionally, field surveys are conducted to gather information about potential sites that could support the design of Thibbun Nabawi treatment centers. This research culminates in a site concept that aligns with the spatial plan of Makassar city, incorporating Islamic architectural concepts such as Habluminallah on the façade, Habluminnas in space processing, and Habluminal-nature in the Herb Garden. Keywords: Islamic Architecture, Makassar, Medicine, Therapy, Thibbun Nabawi.